Absence of Oral Opportunistic Infections in Patients with Inflammatory Bowel Disease Receiving Anti-TNF-α and Anti-Integrin-α4β7 Therapy - Ema Saltović; Brankica Mijandrušić-Sinčić; Alen Braut; Ivana Škrobonja; Ella Sever; Irena Glažar; Sonja Pezelj-Ribarić; Miranda Muhvić-Urek (MDPI AG, 2022)
Biological therapy of inflammatory bowel disease (IBD) carries an increased risk for the development of opportunistic infections due to immunomodulation. The aim of this study was to determine the prevalence and types of oral infections in IBD patients treated with biological (anti-TNF-α and anti-integrin-α4β7) and conventional medication protocols. The study included 20 IBD patients receiving anti-TNF-α therapy, 20 IBD patients receiving anti-integrin-α4β7 therapy and 20 IBD patients without immunomodulatory therapy. Participants completed questionnaires on medical information, oral lesions and symptoms. For each patient, clinical examination and a salivary flow rate test were performed, followed by a swab of the oral mucosa. The swab samples were cultured to identify Candida spp. and oral bacteria. No bacterial opportunistic infections were detected. Candidiasis was detected in four participants, with no significant difference between groups (p = 0.765). Hyposalivation was most common in the anti-TNF-α group, with a significant difference between groups (p = 0.036). There were no significant differences between groups in self-reported oral mucosal lesions and symptoms (p > 0.05), or in the distribution of oral mucosal lesions (p > 0.05). This study suggests that IBD patients receiving biological therapy are at no greater risk of developing oral opportunistic infections than IBD patients not receiving immunomodulatory therapy.